Distribution. W & C Siberia, from the Irtysh River Basin E in Talpidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2018)
Distribution. W & C Siberia, from the Irtysh River Basin E to Baikal region and upper reaches of Lena River Basin, and from Yenisei River at 68-69°30'N S to Altai, Salair, and Sayan Mts, NE Kazakhstan, and NW Mongolia (N Great Lakes Depression and Hovsgol Mts). Published as part of Russell A. Mittermeier & Don E. Wilson, 2018, Talpidae, pp. 52-619 in Handbook of the Mammals of the World – Volume 8 Insectivores, Sloths and Colugos, Barcelona :Lynx Edicions on page 609, DOI: 10.5281/zenodo.6678191